As patentes de genes humanos sob a perspectiva do biodireito e da bioética - Freitas, João Filipe Franco de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This essay is about legal and ethical aspects related to patents of inventions involving human genetic material. The first aim is to demonstrate the difficulties that biotechnological inventions find to fulfil the positive requirements of patentability. It discusses, with regard to novelty, if DNA isolated from the genome is a new composition of matter, or a product of nature. With regard to inventive step, if there is considerable effort by the inventor in gene isolation and if the function assigned to that segment is obvious. With regard to industrial applicability, if the invention can be repeated, the sufficiency of its description and the indication of an effective utility for that specific DNA segment. Based on biolaw, it addresses the impacts on human dignity, the characterization of the genome as the common heritage of mankind, the possibility of commercialization of the human body and the restrictions on the freedom of research. Based on bioethics, it investigates if the genome is endowed with special status that prevents its appropriation, the way in which the respect for the autonomy of people who provide the biological material used in the invention is assessed, and fair and equitable sharing of the benefits of genetic research. The methods used are mainly deductive and inductive. The deductive method was used mainly for the study and understanding of the regulatory framework of the patent system and its connections with biolaw and bioethics. The inductive method was used in order to refer to specific patents, such as the BRCA and CCR5 genes and MSP-1 protein, and to relevant court cases, like AMP v. Myriad, from which more comprehensive judgments on the fulfillment of patentability requirements by inventions involving genetic sequences could be made, and on the ethical implications they entail. At the end, it is affirmed that there is a hypertrophy of patents, which negatively affects the...

O presente trabalho versa sobre aspectos jurídicos e éticos relacionados com as patentes de invenções que envolvem material genético humano. Busca-se, inicialmente, demonstrar as dificuldades que as invenções biotecnológicas encontram para atender os requisitos positivos de patenteabilidade. Discute-se, quanto à novidade, se o DNA isolado do genoma é uma nova composição da matéria ou um produto da natureza. Em relação à atividade inventiva, se há esforço considerável por parte do inventor no ato de isolamento do gene e se se constata obviedade na função atribuída àquele segmento. No que concerne à aplicação industrial, se o invento pode ser repetido, a suficiência de sua descrição e a definição de uma utilidade concreta para aquele segmento de DNA específico. Com base no biodireito, abordam-se os impactos sobre a dignidade humana, a caracterização do genoma como patrimônio comum da humanidade, a possibilidade de comercialização de partes do corpo humano e as restrições impostas à liberdade de pesquisa. Com base na bioética, investiga-se se o genoma é dotado de status especial que impede a sua apropriação, o modo pelo qual se afere o respeito à autonomia das pessoas que fornecem o material biológico empregado no invento e a equidade na repartição dos benefícios da pesquisa genética. Os métodos empregados são principalmente o dedutivo e o indutivo. O método dedutivo foi utilizado, sobretudo, para o estudo e compreensão da estrutura normativa dos sistemas de patentes e de suas conexões com o biodireito e a bioética. O método indutivo foi empregado através da referência a patentes específicas, como as dos genes BRCA e CCR5 e da proteína MSP-1, e a casos judiciais relevantes, tal qual AMP v. Myriad, a partir dos quais puderam ser formulados juízos mais abrangentes sobre o preenchimento dos requisitos de patenteabilidade pelas invenções que envolvem sequências genéticas e sobre as...
Keywords: Direito e biologia; Genoma; Genética humana - Aspectos morais e éticos; Bioética - Aspectos jurídicos; Patentes